Posted by thawk on Monday, November 8, 2010 at 9:13pm.
-3/7x = 6/35
to get x alone, you must divide all terms by the numerical coefficient (the number before the variable) of x, thus:
(-3/7)x/(-3/7) = (6/35)/(-3/7) = -(6/35)/(3/7)
*i just rewrite the negative sign outside*
on the left side, -3/7 will be cancelled, and on the right side, we have a to divide fractions,,
to divide a fraction, first get the reciprocal of the divisor (the 3/7),
reciprocal is just interchanging of numerator and denominator:
3/7 : reciprocal is 7/3
now, the process becomes multiplication:
x = - 6/35 * 7/3
multiply numerator by numerator, and denominator by denominator:
x = -(6*7)/(35*3)
now solve for x,,
hope this helps. :)